Atmospheric OH reactivity in the western United States determined from comprehensive gas-phase measurements during WE-CAN. Issue 1 (9th November 2022) - Permar, Wade; Jin, Lixu; Peng, Qiaoyun; O'Dell, Katelyn; Lill, Emily; Selimovic, Vanessa; Yokelson, Robert J.; Hornbrook, Rebecca S.; Hills, Alan J.; Apel, Eric C.; Ku, I-Ting; Zhou, Yong; et al.
Abstract : Using OH reactivity we assess the major daytime OH radical sinks in western U.S. wildfire plumes and other smoke impacted environments, testing their current model representation while providing a roadmap for future model development. Abstract : Wildfire smoke contains numerous different reactive organic gases, many of which have only recently been identified and quantified. Consequently, their relative importance as an oxidant sink is poorly constrained, resulting in incomplete representation in both global chemical transport models (CTMs) and explicit chemical mechanisms. Leveraging 160 gas-phase measurements made during the Western Wildfire Experiment for Cloud Chemistry, Aerosol Absorption, and Nitrogen (WE-CAN) aircraft campaign, we calculate OH reactivities (OHRs) for western U.S. wildfire emissions, smoke aged >3 days, smoke-impacted and low/no smoke-impacted urban atmospheres, and the clean free troposphere. VOCs were found to account for ∼80% of the total calculated OHR in wildfire emissions, with at least half of the field VOC OHR not currently implemented for biomass burning (BB) emissions in the commonly used GEOS-Chem CTM. To improve the representation of OHR, we recommend CTMs implement furan-containing species, butadienes, and monoterpenes for BB. The Master Chemical Mechanism (MCM) was found to account for 88% of VOC OHR in wildfire emissions and captures its observed decay in the first few hours of aging, indicating that most known VOC OH sinks are included in the explicit mechanisms. We find BB smoke enhanced the average total OHR by 53% relative to the low/no smoke urban background, mainly due to the increase in VOCs and CO thus promoting urban ozone production. This work highlights the most important VOC species for daytime BB plume oxidation and provides a roadmap for which species should be prioritized in next-generation CTMs to better predict the downwind air quality and health impacts of BB smoke.